2015
DOI: 10.1152/ajpendo.00003.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based microassay of2H and13C plasma glucose labeling to quantify liver metabolic fluxes in vivo

Abstract: Mouse models designed to examine hepatic metabolism are critical to diabetes and obesity research. Thus, a microscale method to quantitatively assess hepatic glucose and intermediary metabolism in conscious, unrestrained mice was developed. [(13)C3]propionate, [(2)H2]water, and [6,6-(2)H2]glucose isotopes were delivered intravenously in short- (9 h) and long-term-fasted (19 h) C57BL/6J mice. GC-MS and mass isotopomer distribution (MID) analysis were performed on three 40-μl arterial plasma glucose samples obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 65 publications
15
71
0
Order By: Relevance
“…was increased by 50% in fed Insr LKO mice (Figure 4E) and decreased by 35% in fed Tsc1 LKO mice on a chow diet (Figure 4F). Oxidative metabolism in the TCA cycle was generally decreased by fasting (Figure 4G and H), consistent with a recent study using similar methodology (Hasenour et al, 2015). Insr LKO mice had an overall increase in hepatic TCA cycle flux but remained responsive to nutritional state (Figure 4G).…”
Section: Resultssupporting
confidence: 91%
“…was increased by 50% in fed Insr LKO mice (Figure 4E) and decreased by 35% in fed Tsc1 LKO mice on a chow diet (Figure 4F). Oxidative metabolism in the TCA cycle was generally decreased by fasting (Figure 4G and H), consistent with a recent study using similar methodology (Hasenour et al, 2015). Insr LKO mice had an overall increase in hepatic TCA cycle flux but remained responsive to nutritional state (Figure 4G).…”
Section: Resultssupporting
confidence: 91%
“…However, when a regression model including randomization was used, data from [U- 13 C]lactate/[U- 13 C]pyruvate-perfused livers gave values identical to those from [U- 13 C]propionate and simple equations ( Figure 1G). Hence, in contrast to a recent report (21), but in agreement with another (22), these findings demonstrate that tracer doses of propionate do not perturb glucose production or anaplerosis and explain why [U- 13 C]pyruvate/lactate/alanine tracers provide lower estimates of pyruvate cycling when incomplete randomization is not modeled (23).…”
Section: Introductionsupporting
confidence: 77%
“…This agrees with our previous experience, where we optimized propionate administration in mice to avoid elevated glucose or insulin levels (62). Recently, investigators from the Vanderbilt Mouse Metabolic Phenotyping Center, Vanderbilt University, used an identical tracer approach, but an independent mass spectrometry platform, and found fluxes that were similar to those we previously reported; they also found that tracer amounts of [U- 13 C]propionate had no effect on hepatic metabolic flux in mice when fit to a complete regression model (22). Notably, stoichiometric analysis of oxygen consumption correlated strongly with flux measurements using 13 C and 2 H isotopomer analysis.…”
Section: Validation Of Methodology In Contrast To One Report (21) Tsupporting
confidence: 59%
“…Such high rates of hepatic pyruvate cycling would use a significant fraction of the ATP available, and place the hepatocyte in a metabolically precarious position. In a recent study we found that an intra-arterial infusion of propionate, that was lower than (Hasenour et al, 2015; Jin et al, 2005; Jin et al, 2004; Satapati et al, 2015) or similar to (Sunny et al, 2011) the total amount of sodium propionate administered in previous studies, dose-dependently increased: hepatic propionyl CoA concentrations up to 18 fold, hepatic pyruvate cycling up to 20–30 fold, hepatic TCA intermediates (malate and succinate) and aspartate by 2–3 fold, and rates of hepatic glucose production by up to 2 fold in awake rats (Perry et al, 2016). It is well established that propionyl CoA potently stimulates pyruvate carboxylase activity and flux (Perry et al, 2016; Scrutton, 1974) and this may explain at least in part the large increases in hepatic pyruvate carboxylase flux and pyruvate cycling that Sunny et al observed in their [1,2,3- 13 C 3 ]propionate labeling studies of hepatic mitochondrial metabolism in humans (Sunny et al, 2011).…”
Section: Resultsmentioning
confidence: 91%